Teacher and Student Perspectives on Smart TV-Based Instruction: Implications for Learning Motivation in Islamic Schools - Faridah Faridah; Buhaerah Buhaerah; Abdullah Thahir; Sitti Jamilah Amin; Kaharuddin Kaharuddin (Papanda Publisher, 2026)
The integration of digital technologies in education has prompted renewed interest in Smart TV as an instructional medium, yet limited research examines both teacher and student perspectives on its role in enhancing learning motivation within Islamic secondary education contexts. This qualitative descriptive-interpretive study explored perceptions of Smart TV utilization and its motivational impact at MTsN Pinrang, Indonesia. Data were collected through classroom observations, semi-structured interviews with five teachers and 20 students, and document analysis, then analyzed using reflexive thematic analysis. Findings revealed that teachers perceived Smart TVs as effective tools facilitating multimedia-rich, student-centered instruction and transforming their roles from knowledge transmitters to learning facilitators. Students reported heightened interest, enjoyment, and engagement, with motivational outcomes linked to Smart TV's support for autonomy, competence, and relatedness as theorized in Self-Determination Theory. However, implementation faced infrastructure limitations, increased teacher workload, and occasional cognitive overload among students. Smart TV-based instruction holds substantial potential to enhance learning motivation when aligned with evidence-based pedagogical design and supported by adequate infrastructure and teacher professional development. The study contributes theoretical insights by integrating Cognitive Theory of Multimedia Learning and Self-Determination Theory within Islamic education contexts, while highlighting that technology effectiveness depends on systemic institutional readiness rather than mere technological adoption.